EFL LEARNERS’ PERCEPTION ON THE USE OF MS TEAMS APPLICATIONS - Puji Jayanti (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2021)
The implementation of online learning becomes popular all around the world during the Covid-19 pandemic. In Indonesia, the changing of synchronous learning to asynchronous learning is somewhat new. As a result, the researchers think it is needed to learn about the students' perceptions of online learning with MS Teams in learning to write. The goals of this study were to find out the activities done by the students in using MS Teams, students’ perception toward the use of MS Teams, and the utilization of MS Teams in class. The research used descriptive qualitative research. The eighth-grade students at SMP N 7 Purwodadi were the participant in the study. The data collection used in this study was interviews and questionnaires. Four steps of data analysis namely data collection, data reduction, data display, and data verification were used in the study. The result showed that the students utilized MS Teams to send assignments and discuss with the teacher related to learning writing. The students' perceptions toward the use of MS Teams in learning writing were MS Teams allows students to study anywhere and anytime, MS Teams allows students to practice writing English, and MS Teams helps students to improve their writing skill. The students utilized MS Teams to study for at least two hours per day and to discuss with the teacher. In conclusion, the students' perceptions toward the use of MS Teams in online learning showed positive responses.   Keywords: MS Teams, Perception, Writing Skill, EFL, Online Learning